2016
DOI: 10.1039/c6sc00046k
|View full text |Cite
|
Sign up to set email alerts
|

Whipped oil stabilised by surfactant crystals

Abstract: We describe a protocol for preparing very stable air-in-oil foams containing surfactant crystals starting from a one-phase solution of a fatty acid in a vegetable oil. On cooling, plate-like crystals form which adsorb at air bubble surfaces after aeration of the mixture. Such foams can be destabilised by gradual warming leading to crystal melting and bubble coalescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 48 publications
(54 reference statements)
5
100
1
Order By: Relevance
“…In these studies, amphiphilic substances were employed for forming non-aqueous foams in which air bubbles were entrapped by lamella liquid crystal layers. Further studies have reported on non-aqueous foam constructed by liquid oil and air-stabilizing materials using solid particles [25][26][27] and surfactant crystals [28,29]. However, no study of whipped oil using fat crystals has been done.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, amphiphilic substances were employed for forming non-aqueous foams in which air bubbles were entrapped by lamella liquid crystal layers. Further studies have reported on non-aqueous foam constructed by liquid oil and air-stabilizing materials using solid particles [25][26][27] and surfactant crystals [28,29]. However, no study of whipped oil using fat crystals has been done.…”
Section: Introductionmentioning
confidence: 99%
“…Oil foams, also called oleofoams, non-aqueous foams, or whipped oils, refer to a colloidal dispersion where air bubbles are dispersed in oils (Figure 3d; Heymans et al, 2018), which can be used as low-calorie food products (Gunes et al, 2017) and lubricating oil (Binks, Davies, Fletcher, & Sharp, 2010). Crystalline particles including MAGs (Gunes et al, 2017;Heymans et al, 2018), DAGs (Shrestha, Shrestha, Sharma, & Aramaki, 2008;Shrestha, Shrestha, Solans, Gonzalez, & Aramaki, 2010), TAGs (Binks & Marinopoulos, 2017;Mishima, Suzuki, Sato, & Ueno, 2016), fatty acids (Binks, Garvey, & Vieira, 2016), fatty alcohol (Fameau et al, 2015), and a combination of sucrose ester and lecithin (Patel, 2017d), as well as solid particles such as fluorinated particles (Binks, Johnston, Sekine, & Tyowua, 2015), have been reported to be capable of stabilizing air-oil interface in oil foams. Here, we mainly focus on edible oil foams stabilized by crystalline MAGs and DAGs.…”
Section: Interfacial Propertiesmentioning
confidence: 99%
“…The obtained samples had overrun percentages ranging from 47% to 52% and showed excellent storage stability that could maintain the initial foam volume as long as 2 months. It is believed that the foamability and foamstability of oil foams are determined by the phase behavior (solubility boundary) of crystalline stabilizers in the bulk oil (Binks et al, 2016;Chen, Van Damme, & Terentjev, 2009;Gunes et al, 2017;Shrestha et al, 2006b;Shrestha et al, 2006c;Shrestha, Aramaki, Kato, Takase, & Kunieda, 2006a), which can be controlled by altering types and concentrations of stabilizers, foaming temperature, storage temperature, and bulk oil types (Fameau & Saint-Jalmes, 2017). For example, when foaming temperature is well below the solubility boundary, MAGs or DAGs crystallize into particles to stabilize the air bubbles formed upon whipping.…”
Section: Interfacial Propertiesmentioning
confidence: 99%
“…Stability against disproportionation (an Ostwald ripening-type coarsening in foams) and coalescence is typically provided by Pickering stabilizers (Hunter et al, 2008). Such materials are typically fat crystals (Gunes et al, 2017;Mishima et al, 2016) or surfactant-induced crystals in the fat structure (Binks et al, 2016;Brun et al, 2015). Such mechanisms are reviewed by Fameau and Saint-Jalmes (2017).…”
Section: Introductionmentioning
confidence: 99%